Analyzing Senior High School English Teachers’ Language Perceptions and Practices of the Revised National Curriculum Standards in Southern Sichuan - Wen Jia; Zhao Yaling; Huang Tao (Jurnal Bebasan, 2024)
This study examines high school English teachers' linguistic practices, understanding, and implementation of the National English Curriculum Standards for General Senior High School (2017 edition, revised in 2022) within southern Sichuan, China. Employing a mixed-method approach, the research integrates quantitative and qualitative data to explore how linguistic elements are incorporated into teaching practices. A total of 350 high school English teachers participated in a questionnaire survey, and 20 of them engaged in in-depth, face-to-face interviews to provide qualitative insights. The findings indicate that most teachers exhibit a robust grasp of the revised curriculum's linguistic dimensions, such as syntax, semantics, and discourse strategies. However, areas like integrating cultural awareness into language teaching and developing evaluation methodologies require improvement. This study underscores the significance of linguistic frameworks in curriculum implementation and highlights practical implications for enhancing teacher preparedness to align pedagogical practices with national standards.